The role of open education in improving the accuracy of death certification practices among biomedical professionals - Borges-Ferro, Amadeu (2024)
During the COVID-19 pandemic, mortality data has proven to be a valuable tool in understanding the epidemiological trends and impacts of health policies on a population. The accurate recording, coding, and publishing of information on causes of death is crucial. Despite using an online platform for registering death certificates since 2014, Portugal records a relatively high proportion of deaths attributed to non-useful codes in public health analyses, mainly due to inappropriate certification practices. However, traditional in-person learning formats are not sustainable due to the limited resources available. Aim of the study: As part of the European CODA-EU project (Erasmus+Program), a team of multidisciplinary experts from biomedical, social, and education sciences designed a Multilingual MOOC on certification on the causes of death. It targets health professionals, such as Biomedical Scientists, for whom competencies in cause-of-death certification are important.